The complete guide to the gap year : the best things to do between high school and college - White, Kristin, 1972- (Jossey-Bass, 2009)
This is the go-to book for anyone considering a year to re-charge, to follow a passion, to become immersed in another culture, or to find their love of learning again. It includes everything a student, parent, or guidance counselor would want to know about the gap year; including what a gap year is, what it is not, and why it can have a positive impact on a young life. Readers can find out what college admissions deans think of the gap year, and how it is becoming an important part of the educational process at top tier universities. Economically, the gap year can make a lot of sense in a recession, and this useful guide gives information on free programs, financial aid, and tax savings. The book has a comprehensive guide to 200 of the world's best gap year programs. Students will find self-quizzes and helpful criteria to help them decide whether to take a gap year, and if so what kind of program. This guide helps them evaluate their interests and plan and fund their gap year; whether it means spending a year on a sailing vessel, coaching sports and teaching in an impoverished area, or following a passion in the arts or academics.